Instrumentation failure during microlaryngoscopy. Issue 4 (25th April 2022) - van den Berg, Nadia; Corbett, Mel; Cleere, Eoin; Keogh, Ivan
Abstract: Equipment failure can be a cause of morbidity during surgical procedures. We present two cases where a broken surgical instrument, a heart-shaped curved micro-grasper, colloquially termed 'sweetheart' micro-forceps, compromised patient safety during microlaryngoscopy. We discuss the importance of thorough safety protocols and communication between team members to mitigate this risk. Microinstruments used during microlaryngoscopy are at risk of failure or breakage due to their small size. Surgeons must be alert to the risk of equipment failure during surgery as a potential cause of patient morbidity. In our patient, loss of the broken instrument in the respiratory tract could have resulted in iatrogenic aspiration, respiratory infection and would have necessitated rigid bronchoscopy for removal. Instruments and equipment must checked and communicated by the surgical team before and after use to prevent potential patient morbidity.